Storage Stability of Fermented Finger Millet (Eleusine coracana) Packaged in PVC Container under Ambient Conditions - Karki, Dhan Bahadur; Kharel, Ganga Prasad (Journal of Food Science and Technology Nepal, 2009)
Effects of PVC container packaging on the chemical and sensory quality of fermented millet under ambient condition were studied. Finger millet was fermented for 15 days at room temperature (25 ±2ºC) using defined fermentation starter, packaged in PVC container and stored at room temperature for 90 days and analyzed for chemical and sensory characteristics as compared to the control (Stored at -300ºC, 0 day). Moisture content; total, fixed and volatile acidities and total sugar did not differ while alcohol content decreased significantly (p < 0.05) in room temperature stored sample (14.4 % v/m) compared to control (13.1% v/m). A significant increase in total soluble solids, reducing sugar, total aldehydes and ester contents occurred in 90 days stored sample. Sensory evaluation revealed that remarkable improvement on color, taste and smell of the millet and occurred in room temperature stored millet than that of control counterpart. Hence, PVC could be a promising packaging container in extending the shelf-life of fermented millet. Key words: Fermented millet; PVC container; Storage stability; Chemical and Sensory quality Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 70-71